DEFERENSIFIKASI DAN DIVERSIFIKASI PRODUK DALAM PENGEMBANGAN PRODUK TOUR BPW - Rachmadi, Hari (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2008)
The meaning of diversification and diferensification product is to make a product with kinds of variety subject and other subyek (tourism object). Fasility or service so it look all product have her own specialization the is sport, cultural, and adventure so it make more kinds of interesting product. The diversification and deferensification product is useful to increase service and sales tour package in travel agent, because that can make change at tour package more variety and more interest. The metode is to fix up all of componen more better. So the diversification and deferentification product very important to realization.